Italian Real-Life Experience of Patients with Hereditary Transthyretin Amyloidosis Treated with Patisiran - Di Stefano V; Fava A; Gentile L; Guaraldi P; Leonardi L; Poli L; Tagliapietra M; Vastola M; Fanara S; Ferrero B; Giorgi M; Perfetto F; et al. (Dove Medical Press, 2022)
Vincenzo Di Stefano,1 Antonella Fava,2 Luca Gentile,3 Pietro Guaraldi,4 Luca Leonardi,5 Loris Poli,6 Matteo Tagliapietra,7 Michele Vastola,8,9 Salvatore Fanara,1 Bruno Ferrero,10 Mauro Giorgi,2 Federico Perfetto,8 Massimo Russo,3 Domitilla Russo11 1Department of Biomedicine, Neuroscience and Advanced Diagnostic (BIND), University of Palermo, Palermo, Italy; 2Division of Cardiology, Heart Vascular and Thoracic Department, Città della Salute e della Scienza (Molinette Hospital- University of Turin), Turin, Italy; 3Unit of Neurology and Neuromuscular Disease, Department of Clinical and Experimental Medicine, University of Messina, Messina, Italy; 4IRCCS Istituto delle Scienze Neurologiche di Bologna, Bologna, Italy; 5Department of Neuroscience, Mental Health and Sensory Organs (NESMOS), Sapienza University of Rome Sant'Andrea Hospital, Rome, Italy; 6Department of Neurology, ASST Spedali Civili, Brescia, Italy; 7Department of Neurosciences, Biomedicine and Movement Sciences, University of Verona, Verona, Italy; 8Tuscan Regional Amyloidosis Centre, Careggi University Hospital, Florence, Italy; 9Neurosciences Department, Florence University, Rome, Italy; 10SC Neurology 2U, Department of Neuroscience "Rita Levi Montalcini", Città della Salute e della Scienza (Molinette Hospital -University of Turin), Turin, Italy; 11Division of Cardiology, Department of Clinical and Molecular Medicine, St. Andrea Hospital, Sapienza University, Rome, ItalyCorrespondence: Vincenzo Di Stefano, Department of Biomedicine, Neuroscience and advanced Diagnostic (BIND), University of Palermo Palermo, Italy, Via del Vespro 143, Palermo, 90127, Italy, Tel +39 3285781786, Fax +390916552974, Email vincenzo19689@gmail.comAbstract: Hereditary transthyretin amyloidosis (ATTRv) is a multisystemic, rare, inherited, progressive and adult-onset disease, affecting the sensorimotor nerves, heart, autonomic function and other organs. The actual scenario of pharmaceutical approaches for ATTRv amyloidosis includes five main groups: TTR stabilizers, TTR mRNA silencers, TTR fibril disruptors, inhibitor of TTR fibril seeding and gene therapy. Patisiran is a small, double-stranded interfering RNA encapsulated in a lipid nanoparticle, able to penetrate into hepatocytes, where it selectively targets TTR mRNA, reducing TTR production. We report and discuss 9 cases of different patients with ATTRv amyloidosis successfully managed with patisiran in the real clinical practice. Literature data, as well as the above presented case reports, show that this drug is effective and safe in improving both neurological and cardiovascular symptoms of ATTRv amyloidosis, and to maintain a good QoL, independently form the stage of the disease and the involved mutation. Recent studies correlated improved functional and biochemical outcomes with a regression of amyloid burden, especially at the cardiac level. Today, patisiran can be considered a valid therapeutic option for the management of patients with ATTRv amyloidosis and polyneuropathy and cardiovascular symptoms.Keywords: hereditary transthyretin amyloidosis, patisiran, real-life, case reports